PEMETAAN POTENSI EKOWISATA DI DESA TANJUNG BELIT DAN DESA LUBUK BIGAU KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR PROVINSI RIAU - Rinaldi Zen, Abdullah; Sadjati, Emy; Ikhwan, Muhammad (Wahana Forestra: Jurnal Kehutanan, 2018)
The research entitled "Potency Mapping Of Ekowisata In Tanjung Belit Village And Village Power Of Bigau Kampar Kampar Kuli Hulu Kampar Kampar Provinsi Riau", with the formulation of problem how effort in inventory and mengetekan natural tourism potential object. The purpose of this research is to inventory and map the potential objects of nature tourism. This research use survey method or direct visit to research object. Sources of data used are primary and secondary data obtained from the observation and taking coordinates and tracks in the field, as well as the map of the earth Indonesia indonesia subdistrict kampar left upstream. Data were analyzed using descriptive analysis method. The theoretical basis used is tally sheet guidance of object analysis and natural attraction of Directorate General PHKA 2003 and also software ArcGis 10.1. Based on data analysis, the result of this research is information of 5 potential objects of natural tourism, namely: (1) waterfall cotton stem 150 m, (2) cotton stem waterfall 50 m, (3) waterfall stone wall 1, ( 4) rock waterfall wall 2, and (5) water surfing. As well as a potential map that contains information about potential objects of natural tourism.